The Problems of Generating Ideas Faced by English Language Students in Research Proposal Writing - Sary Eka Wahyuni; Nina Inayati (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
Generating ideas plays the key role in the initial phase of writing process, but not many empirical research is available in the literature that address the problems that students face in generating ideas, especially during research proposal writing. The current study aims to find out students’ problems in generating ideas in writing the research proposal. This descriptive study mainly collected the data through survey and interview involving seventh semester students who were in their initial phase of drafting research proposal for their final projects. The data were then analyzed and presented using descriptive quantitative method. The findings indicate that most of the students’ reported facing problems when generating ideas during the initial phase of research writing. Data analysis show that the problems range from the topic development, theoretical frameworks identification, relevant theory search, trusted sources evaluation, research ideas and relevant theory connection, as well as problems and theory assessment. Some pedagogical implications in light of the findings are discussed following the presentation of the results of the study, such as the importance to provide constructive feedback in a timely manner, and discussing ways to evaluate quality resources.